One piece. Collection no. 11 [videorecording (DVD)] ([Publisher not identified], 2014)
Sanji stows away aboard the Sea Train, only to be joined in his battle against the CP9 goons by the heroic Soge King, a wandering warrior from the Island of Snipers! With the storm of all storms bearing down upon him, Chopper mounts a courageous rescue attempt in the rapidly rising waters. As the foreboding fortress of Enies Lobby draws ever closer, Luffy launches an impulsive attack that could spell doom for everyone!